Aplicações dos teoremas de ponto fixo para equações diferenciais parciais - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
In this work, we present and prove the ﬁxed-point theorems of Banach, Schauder, and Schaefer, and the later we applied in the resolution of three nonlinear problems, we also study the Sobolev Spaces, fundamental for testing the existence and uniqueness of soluti ons in Partial Diﬀerential Equations. The Banach Fixed-Point Theorem for contractions is applied to prove the existence of a solution in a diﬀusion and reaction system, whereas the ﬁxed-point theorems of Schauder and Schaefer are used to solve two problems of el liptic equations, respectively, semilinear and quasilinear.
Keywords: Equações diferenciais parciais; Teoremas do ponto fixo; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA